Genetically encoded proton sensors reveal activity-dependent pH changes in neurons - Raimondo, Joseph V.; Irkle, Agnese; Wefelmeyer, Winnie; Newey, Sarah E.; Akerman, Colin J. (Frontiers in Molecular Neuroscience, 2012)
The regulation of hydrogen ion concentration (pH) is fundamental to cell viability, metabolism and enzymatic function. Within the nervous system, the control of pH is also involved in diverse and dynamic processes including development, synaptic transmission and the control of network excitability. As pH affects neuronal activity, and can also itself be altered by neuronal activity, the existence of tools to accurately measure hydrogen ion fluctuations is important for understanding the role pH plays under physiological and pathological conditions. Outside of their use as a marker of synaptic release, genetically encoded pH sensors have not been utilised to study hydrogen ion fluxes associated with network activity. By combining whole-cell patch clamp with simultaneous two-photon or confocal imaging, we quantified the amplitude and time course of neuronal, intracellular, acidic transients evoked by epileptiform activity in two separate in vitro models of temporal lobe epilepsy. In doing so, we demonstrate the suitability of three genetically encoded pH sensors: deGFP4, E2GFP and Cl-sensor for investigating activity-dependent pH changes at the level of single neurons.